Innovation of BATIK (Plastic Bricks): Utilizing Plastic Waste as an Environmentally Friendly Business Opportunity - Kirom, M. Fuadil; Ramadhania, Fadila; Elingga, Pinatih Diening; Gusmiarni, Aulia; Maula, Fina Fairuzatul; Zafiroh, Aida; Luluardi, Yunas Derta (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
The increasing problem of plastic waste has become a serious environmental challenge, particularly due to its non-biodegradable nature and its negative impact on ecosystems. On the other hand, the demand for construction materials such as paving blocks continues to grow along with infrastructure development. This study aims to examine the utilization of plastic waste as an alternative material in the production of environmentally friendly paving blocks with economic value for the community. The method used in this study is the Participatory Action Research (PAR) approach, which actively involves the community through stages of observation, planning, training implementation, evaluation, and reflection. The study was conducted in Rengas Village, Kedungwuni District, with waste collectors as the research subjects. Data were collected through observation, pre-test, post-test, and practical assessments to measure improvements in participants' knowledge and skills. The results show that the utilization of plastic waste in paving block production produces materials that are lighter in weight, have lower water absorption, and exhibit good wear resistance. In addition, there was an improvement in community knowledge and skills in plastic waste management. From an environmental perspective, this innovation contributes to reducing the volume of plastic waste, while economically it can reduce production costs by approximately 25% and create new business opportunities for the community. In conclusion, the use of plastic waste as a material for paving blocks has significant potential as an innovative solution for waste management while supporting sustainable development based on a circular economy.